2002
DOI: 10.1046/j.1365-2524.2002.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of pain in older people within the nursing home: a preliminary study

Abstract: The provision of continuing care for older people has largely shifted from the hospital setting to the community, and nursing homes increasingly provide support for older people, many of whom exhibit multiple pathology and complex health and social care needs. However, the quality of pain management within this setting has been identified as an issue of concern. It has been estimated that approximately two-thirds of people aged 65 years and over experience chronic pain, and that the prevalence of chronic pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
2
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 26 publications
(35 reference statements)
3
59
2
8
Order By: Relevance
“…Figures for the USA suggest between 37-47% (Ferrell et al 1990, Horgas & Tsai 1998, Parmalee et al 1993. Similar figures have been reported by investigators within the UK (Allcock et al 2002, Schofield 2005. As there appears to be around 50% of the care home population that are cognitively impaired it is quite worrying that they could be neglected within the literature as they are potentially unable to articulate their pain and this could suggest the potential for poor pain control, or pain control that is not tailored to their specific needs.…”
Section: Introductionsupporting
confidence: 65%
“…Figures for the USA suggest between 37-47% (Ferrell et al 1990, Horgas & Tsai 1998, Parmalee et al 1993. Similar figures have been reported by investigators within the UK (Allcock et al 2002, Schofield 2005. As there appears to be around 50% of the care home population that are cognitively impaired it is quite worrying that they could be neglected within the literature as they are potentially unable to articulate their pain and this could suggest the potential for poor pain control, or pain control that is not tailored to their specific needs.…”
Section: Introductionsupporting
confidence: 65%
“…(2007) views pain assessment as integral to the development of an optimal pain management plan. Standardised assessment tools are used to improve the identification and assessment of pain (Allcock, McGarry & Elkan, 2002).…”
Section: Pain Managementmentioning
confidence: 99%
“…However, the failure of organisations to provide standardised pain assessment tools was identified in a study of 65 nursing homes in the United States, where it was found that 75% of those nursing homes did not use a standardised pain assessment tool (Allcock et al, 2002).…”
Section: Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For all these reasons, musculoskeletal disorders may be regarded as low priority complaints, resulting in less attention to assessment and management by carers and clinicians [7]. Adding to these challenges, assessing pain and the symptoms of musculoskeletal disorders can be difficult in the older population, complicated by cognitive decline, co-morbidities and environmental barriers which people can have in accessing healthcare services [11,12].…”
Section: Introductionmentioning
confidence: 99%